Traffic medicine and first aid: interlocutions with the training of the traffic instructor - Pissaia, Luís Felipe; Costa, Arlete Eli Kunz da (Research, Society and Development, 2020)
The aim of this study is to share an experience report on the realization of the traffic medicine and first aid module of a traffic instructor training course. It is an experience report, with a qualitative, descriptive and exploratory approach, with participants, 13 students from the traffic medicine module and first aid from a traffic instructor training course. Data collection took place through a questionnaire, which was subsequently analyzed with approximations from Bardin’s Content Analysis (2016). Throughout the research, ethical guidelines for research with human beings were followed and respected. The results followed the transversality of the module, intuiting about the interaction of the participants with the classes, discussing the methodology used and the presence of aspects of the relationship between theory and practice. It was also observed the interrelation of the content presented and the importance for personal life. Also, the importance of the module for professional training was identified, under the premise of quality in teaching future vehicle drivers. Thus, it is understood the importance of the module of traffic medicine and first aid for the training of the traffic instructor, being a fundamental profession for the training of vehicle drivers.